Meloxicam and Dexamethasone Administration as Anti-Inflammatory Compounds to Sows Prior to Farrowing Does Not Improve Lactation Performance - Kate J. Plush; John R. Pluske; David S. Lines; Cameron R. Ralph; Roy N. Kirkwood (Animals, 2021)
The aim of this experiment was to determine whether administration of an anti-inflammatory compound to sows prior to farrowing would, via reduced pain and inflammation, increase piglet survival and growth. At day 114 of gestation, multiparous sows were randomly allocated to one of the following treatments: Control (n = 43), which received 10 mL saline, NSAID (n = 55) which received 0.4 mg/kg meloxicam and SAID (n = 54) which received 0.1 mg/kg dexamethasone. Treatments were applied again on day 116 if farrowing had not occurred. There was no treatment effect on piglets born alive or dead from parity two to four sows but in those of parity five and older, NSAID administration reduced the number of piglets born alive and increased the number of piglets born dead (p < 0.05). Sow rectal temperature and incidence of mastitis were unaffected by treatment (p > 0.05). Lactation day two plasma concentrations of cortisol, prostaglandin F2 alpha metabolite and haptoglobin did not differ among treatments (p > 0.05). Treatment effects were not observed in liveborn piglet mortality at any age, or litter weight at day 21 (p > 0.05). Average feed intake during lactation was increased by both NSAID and SAID treatments (p = 0.001). The use of meloxicam prior to farrowing should be avoided as it reduced the number of piglets born alive and did not improve piglet survival and growth.